Interactive simulation of flocking algorithms and game artificial intelligence - Ng, Jack Pei Sheng. (2013)
Navigation of agents in a computer game requires some form of navigation map so that standard path-finding algorithms like A* search can be used to find a route. The FAME library is useful for rapid development of games which requires flocking behaviours in agents. However, it is lacking in having a navigation system that is able to have a formation react to dynamic obstacles as a group instead of breaking up to overcome the obstacle. For example, in a military simulation, it might be desired to have the entire group stay in formation while manoeuvring from one point to another even when faced with an obstacle.